2016
DOI: 10.1371/journal.pone.0153004
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Ten Italian Horse Breeds through Mitochondrial DNA

Abstract: BackgroundThe climatic and cultural diversity of the Italian Peninsula triggered, over time, the development of a great variety of horse breeds, whose origin and history are still unclear. To clarify this issue, analyses on phenotypic traits and genealogical data were recently coupled with molecular screening.MethodologyTo provide a comprehensive overview of the horse genetic variability in Italy, we produced and phylogenetically analyzed 407 mitochondrial DNA (mtDNA) control-region sequences from ten of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 46 publications
7
47
1
Order By: Relevance
“…In consideration of the high diversity of D-loop region, these results can only show a tendency of haplogroup distribution in regions or breeds. Significant geographical separation or breeding effects on the haplogroup structure can only be detected in exceptional cases like breed isolation, limited number of founders as well as extremely rare haplotypes (Cardinali et al, 2016;McGahern et al, 2006a,b). The lack of such specific haplotypes and the wide variability in Kabardian horses precludes a classification into a region or a group of breeds.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In consideration of the high diversity of D-loop region, these results can only show a tendency of haplogroup distribution in regions or breeds. Significant geographical separation or breeding effects on the haplogroup structure can only be detected in exceptional cases like breed isolation, limited number of founders as well as extremely rare haplotypes (Cardinali et al, 2016;McGahern et al, 2006a,b). The lack of such specific haplotypes and the wide variability in Kabardian horses precludes a classification into a region or a group of breeds.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…The lack of such specific haplotypes and the wide variability in Kabardian horses precludes a classification into a region or a group of breeds. But the very high mitochondrial haplotype diversity in horses is a well-known fact (Cardinali et al, 2016;Gemingguli et al, 2016). Multiple, widespread and repeated domestication of diverse founder mares as well as mixed origin of most breeds are considered as likely causes for this phenomenon (Cozzi et al, 2004;McGahern et al, 2006a;Lei et al, 2009).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Conducted studies have shown that most of the dam families of the domestic population of thoroughbred horse breed belong to haplogroups I (4,11,13) or L (3,4,5,6,10,16,17,27), which is clearly demonstrated by the dendrogram in Figure 1. The largest family in the world ranking such as 1 Tregonwell`s Natural Barb Mare family was represented by 6 mares of three different branches in our study.…”
Section: Resultsmentioning
confidence: 91%
“…A comparative analysis of mitochondrial DNA in different populations and horse breeds of Europe and Asia and the phylogenetic reconstruction made on its basis showed the presence of complex variability of mitochondrial haplogroups [3][4][5][6] in horses. This was not observed in other domesticated species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Y chromosome (for paternal history) and the mitochondrial DNA (mtDNA) (for maternal history) were used in the evolutionary, phylogeographic and genetic diversity studies [9][10][11][12][13] . In a study conducted in the United States, mtDNA sequence analyses were found to be useful in eliminating doubts about the origin of horses, other than biological characteristics, and they may also be used in solving problems based on traditional assumptions about Arabian horses with a close common ancestry [14] .…”
Section: Introductionmentioning
confidence: 99%